Mathematical Problem Solving Skills: Comparison of Guided Discovery Learning Models and Problem Based Learning Models: Kemampuan Pemecahan Masalah Matematis: Perbandingan Model Guided Discovery Learning dan Model Problem Based Learning - suci rahma putri (International Journal of Technology Vocational Education and Training, 2020)
The purpose of this study was to examine the achievement of mathematical problems solving ability between students who acquired learning with Problem Based Learning model with students who acquired learning with Guided Discovery Learning model. This research was a mixed method research with concurrent embedded method. This research consists of experimental group that obtained learning with Guided Discovery Learning method and Problem Based Learning method. The population of this research was a junior high school students in Tanah Datar regency, West Sumatera with sample of grade VIII. Data analysis was done quantitatively and qualitatively. Quantitative analysis was used to calculate the difference in the achievement of mathematical problem solving ability, while qualitative data analysis was used to strengthen the result of quantitative analysis. The results showed that the percentage of the achievement of mathematical problem solving ability of students who obtained learning with Guided Discovery Learning method and Problem Based Learning method is moderate, whereas there is no difference in the achievement of significant mathematical problem solving ability between the two experimental classes.